Perception of the multidisciplinary team about care for children and adolescents who are victims of violence (Research, Society and Development, 2020)
To know the perception of the multidisciplinary team about the care provided to the child and adolescent victim of violence. This is an integrative review of literature based on 15 articles published in the period between 2012 to 2017 in the databases SCIELO, LILACS and BDENF. These were separated and categorized, interconnecting them to obtain a set of propositions and conclusions from the selected authors. The assistance provided by the multidisciplinary team is hampered by poor professional training, excessive workload, fear of reprisals by the aggressors and lack of support from referral mechanisms. Prevention strategies coupled with the existence of a support network for professionals would be able to reduce errors in the diagnosis and treatment of the phenomenon in question, thus, the professionals being trained and the committed sectors could guarantee the rights to the healthy development of these children and adolescents.